Efficiency of an Otto engine under alternative power optimizations - Gumus, Metin; Atmaca, Mustafa; Yimaz, Tamer (JOHN WILEY & SONS LTD, 2009)
The proper optimization criterion to be chosen for the optimum design of the heat engines may differ depending on their purposes and working conditions. In this study, a comparative performance analysis is carried out for a reversible Otto cycle based on three alternative performance criteria namely maximum power (mp), maximum power density (mpd) and maximum efficient power (mep). The power density criterion is defined as the power per minimum specific volume in the cycle and the efficient power criterion is defined as multiplication of the power by the efficiency of the Otto cycle. Maximizing the efficient power gives a compromise between power and efficiency. Three different objective functions are defined and maximization of these functions is carried out under different design parameters of the Otto engine. The variations of power, power density and efficient power outputs are derived and presented with respect to the thermal efficiency of the cycle for various temperature ratios. It has been found that the design parameters at mep conditions lead to more efficient engines than that at the mp condition and the mep criterion may have a significant power advantage compared with mpd criterion. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: performance optimization; power optimization; heat engine; Otto cycle; JOULE-BRAYTON ENGINE; VARIABLE SPECIFIC-HEATS; ENDOREVERSIBLE OTTO; WORKING FLUID; THERMODYNAMIC CYCLES; MAXIMUM POWER; COMBUSTION; MODEL; CRITERION; Energy & Fuels; Nuclear Science & Technology